Туктымысь пи: очерк : [для среднего и старшего школьного возраста] / Михаил Лямин - Лямин Михаил Андреевич (Удмуртия, 1988)
Экземпляры: ЦГДБ (20200113) / Инвентарный номер: 29710 / Цена: 00.25 / Сис.шифр: 84(2Рос- Удм) / Авт.знак: Л 97 / ГРНТИ: 17.82.40 / ББК: 84(2Рос- Удм)